(Dis)continuity in modern conservation as a problem in professional and social context - Špikić, Marko (2012)
History of conservation in the past 120 years testifies to the richness of a specific history of ideas. On the other hand, it hasn’t always been a linear or evolutionary process, but is marked by great hopes, prophecies and disillusions, by ideals of correctness and longevity, and harsh realitiy of discontinuities after world conflicts. Dealing with William Morris and Camillo Boito, the historian of conservation is facing “modernist” language expressing latent professional and social revolutions, and dealing with (pre)avant-garde discourses of the coming of a new era, present even in the work of a cautious writer such as Alois Riegl. The fin-de-siècle generation of conservation theorists opened new paths. The question was (and, in my opinion, still is): can they still to be considered our predecessors, or models? Bearing in mind the contemporary dilemmas when dealing with concepts of authenticity, age-value, and plurality of expression in the object of conservation, we can also ask ourselves: were abovementioned writers only protagonists of a distant history, unconnected to us? Or, could they still be considered a vital part of the pre-history of our culture of conservation? The presentation will discuss the problem of continuity in conservation as a history of ideas, with socio-politically justified ruptures.